Mycobacterium marinum osteomyelitis of a long bone. - Sivan, M; Bose, D; Athanasou, N; McNally, M (2008)
Mycobacterium marinum can uncommonly cause osteomyelitis of small bones of extremities. The reported cases in literature are reviewed. We report a rare case of long bone osteomyelitis which as far as we are aware, has never been described before. Even though this organism normally causes infection in the superficial cooler regions of the body, clinicians should be aware of the possibility of long bone osteomyelitis in patients with a history of immune compromise and the appropriate treatment strategy in such cases.